Chronic severe pyloric lesions in horses: 47 cases. (28th August 2019) - Bezdekova, B.; Wohlsein, P.; Venner, M.
Summary: Background: The clinical findings and outcome associated with chronic severe equine pyloric lesions have not been well described previously. Objectives: To describe the history, clinical signs, endoscopic and ultrasound results, laboratory data, treatment, pathological findings and survival of horses with chronic severe pyloric lesions. Study design: Retrospective case series. Methods: Medical records from horses treated at clinics in Czech Republic and Germany in which chronic severe pyloric lesions were confirmed endoscopically and/or on post‐mortem examination were reviewed. Results: Forty‐seven horses were identified, median age 3 years (range 0.8–16 years). There were 3 geldings, 23 mares and 19 stallions and the majority were Warmbloods (60%). The most common presenting signs were poor body condition (40; 87%), slow eating (39; 83%), recurrent colic (35; 74%) and selective appetite (30; 64%). The most consistent laboratory abnormality was hypoalbuminaemia (10; 36%). Slow gastric emptying was confirmed in 29 individuals during gastroscopy and/or ultrasonography. Endoscopy revealed distal oesophagitis in 9 of 47 horses, and severe equine squamous gastric disease in all cases. Pyloric lesions were depressed, flat or raised fibrinosuppurative pyloric ulcers and were seen in 45 (2 pylori were not seen endoscopically). Thirty‐two cases were treated, with 28 responding well initially. All treated cases received anti‐ulcer medication and four underwent gastrojejunostomy. Clinical signs recurred after medical treatment in at least 11 cases. Only 18 of 44 cases (41%) survived long term (3 were lost to follow‐up). Horses diagnosed at 3 years of age or younger were significantly less likely to survive more than 6 months than older horses (27.8% vs. 72.2%, P<0.001). Main limitations: The study is retrospective, some records were incomplete and case identification was subjective. Conclusions: Chronic severe pyloric lesions can be associated with delayed gastric emptying identified with ultrasonography and/or endoscopy. The prognosis is poor in young horses.